Police reform and the transnational circulation of police models: the Portuguese case in the 1860s - Gonçalves, Gonçalo Rocha (Crime, Histoire & Sociétés / Crime, History & Societies, 2014)
This article examines the reform of the Portuguese police system during the 1860s. In this period, the nature of police institutions, functions and practices became a main political issue with the reform movement culminating in the founding of Polícia Civil in urban settlements in 1867 while failing in a project to establish a national gendarmerie. However, this still represented more than just institutional reform ; at stake was a re-examination of police functions, with a new notion of ‘public safety’ and the rationales behind policing practices, with ‘prevention’ and ‘emergency’ as the new guiding concepts. The article concludes that in Portugal, the political culture and the circulation police models between national jurisdictions provide better explanations for police reform than actual concerns about disorder and crime.